Immunotropic effects of nitrogenous metabolites in healthy humans - Kuchma, Igor; Gozhenko, Anatoliy; Ruzhylo, Sofiya; Kovalchuk, Galyna; Nahurna, Yaryna; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2021)
Background. We have previously shown that nitrogenous metabolites have immunomodulatory effects, both in healthy rats and in humans exposed to pathogenic influences. The purpose of this study is their immunotropic activity in clinically healthy people. Materials and Methods. The object of observation were 27 men (aged 24-63 ys) and 14 women (33-62 ys). The plasma levels of the nitrogenous metabolites and parameters of immunity twice with an interval of 5 days was performed. Results. Judging by the multiple correlation coefficient uric acid exhibits maximal immunotropic activity (R=0,665), followed by creatinine (R=0,596) and urea (R=0,541), and closes the constellation of metabolites bilirubin, with the activity of conjugated bilirubin predominating over that of unconjugated (0,539 vs 0,484). Nitrogenous metabolites together upregulate the level in the blood of B-lymphocytes, CIC, IgG, IL-1, eosinophils and monocytes, as well as most parameters of phagocytosis by neutrophils Staph. aureus and E. coli. Instead, they downregulate the phagocytosis activity of Staph. aureus, the relative content of rod-shaped neutrophils, lymphocytes in general and NK-, T active and 0-Lymphocytes in particular. Downregulation of 0-Lymphocytes reflects upregulation of receptor expression, apparently CD22. Conclusion. Nitrogenous metabolites exhibit immunotropic activity in both healthy rats and humans, as well as in patients.